Academic staff recruitment and retention strategies at the University of Limpopo - Mokoditoa, Jocelyn Molly (University of Limpopo (Turfloop Campus), 2011)
The paper examines the causes of the high turn-over rate and the non-retention of the academic staff at the University, and come up with possible solutions to curb the problem. The study addresses the factors that affect the academic staff recruitment and retention strategies. The paper further address identification of factors contributing to the high turnover rate of the academic staff at the University of Limpopo, analyze causes of the problems, work on the feedback obtained from interviewees, and make recommendations that will enable the University to come up with possible and implementable strategies for the recruitment and retention of the academic staff. This was evident by the results of the study through the literature review and the interviews held that academic staff recruitment and retention is a problem. It is therefore advisable for the University to take note of the results of this study, and that there should be a turn-around strategy that could be implemented and monitored. The Human Resource department should have a database that tracks the career path of all academic staff, and notify all appointees who are coming up for tenure. This notice could go out at the start of the last but one year before the appointees become eligible for appointment with tenure. The university must develop a culture of reasonable, clearly articulated, and enforced deadlines for processing applications for promotion. Human Resources department have a role to play in the promotion process as well. Access to information about the promotion process can be enhanced by revamping the websites for some of the institutions which are not really helpful in this respect. Relevant documents (e.g., conditions of service, appointment and promotion guidelines, benefits) can then be made accessible via institutional websites in a very organized manner than is currently the case in many universities
Thesis (MPA)--University of Limpopo, 2011
Keywords: Employee retention; Employee recruitment; 658.3140968; Personnel management - South Africa; Employees - South Africa - Recruiting